(untitled) (Revista Argentina de Musicología, 2019)
Two kinds of music: the one that we play and the one that we hear. Neither signification nor representation: from gesture to sound and from sound to affect. The musical body as experimentation. Prostheses and artifices of the musical body 1: composition. Composition as a construction of a body. Listening to Schumann’s body. Kinetic, energetic and temporal dimensions of music. Music notation: fragmentation of the gesture and opening of possibles. The continuity of the heterogeneous: Lachenmann. Heterochrony of musical time. Write down the gesture: Kurtág. The gesture as objectile: the truth of variation. Prostheses and artifices of the musical body 2: the computer. Risset / Grisey / Dufourt: sound as creation and becoming. Corporeity and sound energy: Lachenmann. The happiness of the movement: Kurtág. Gesture and expense. Against narrativity and topics. The movement of images: Kurtág. Simulacrum and construction of similarity. Movement, gesture, forces: towards the sensation. The little match girl: the sound body and the forces of death.